Perbandingan Inklusi Keuangan di Indonesia dan Filipina - Izzun Khoirun Nissa (Department of Islamic Banking, 2022)
In today's era, financial inclusion becomes an important thing for policy makers. They prioritize formulating a country's financial policies to build an inclusive financial system. The World Bank has recognized that financial inclusion covers 7 of the 17 sustainable development goals (Sustainable Development Goals). The method used in this research is panel data regression. By concluding that in terms of income, Indonesia and the Philippines show the same results where the three indicators of formal account, formal saving, and formal credit have a significant effect on income. This shows that the richer a person is, the higher the financial inclusion. Employment affects financial inclusion. Research in Indonesia and the Philippines shows the same results where work has an effect on formal accounts and formal savings. So it can be concluded that people who work have an effect on increasing financial inclusion compared to those who do not work. Di era saat ini, inklusi keuangan menjadi suatu hal yang penting bagi para pembuat kebijakan. Mereka memprioritaskan menyusun kebijakan keuangan suatu negara untuk membangun sistem keuangan yang inklusif. Bank Dunia telah mengakui bahwa inklusi keuangan mencakup 7 dari 17 tujuan pembangunan berkelanjutan (Sustainable Development Goals). Metode yang digunakan dalam penelitian ini yaitu regresi data panel. Dengan memberikan kesimpulan bahwa dalam hal pendapatan, Indonesia dan Filipina menunjukkan hasil yang sama di mana ketiga indikator formal account, formal saving, dan formal credit berpengaruh signifikan terhadap pendapatan. Hal ini menunjukkan semakin kaya seseorang akan menaikkan inklusi keuangan. Pekerjaan berpengaruh terhadap inklusi keuangan. Penelitian di Indonesia dan Filipina menunjukkan hasil yang sama dimana pekerjaan berpengaruh terhadap formal account dan formal saving. Sehingga dapat disimpulkan bahwa orang yang bekerja berpengaruh meningkatkan inklusi keuangan di banding mereka yang tidak bekerja.